Distributive trade and economic growth: EU28 evidence for the period 2008-2015 - Sokolov Mladenović, Svetlana; Mladenović, Igor; Ćuzović, Djordje (Journal of Business Economics and Management, 2019)
The purpose of this paper is to appoint the causality between economic activity in the sector of distributive trade and the economic growth of 28 European Union nations. Specifically, it examines the impact of changes in turnover per employee in the distributive trade sector in EU member states on the tangible economic growth rate. The determination to adopt this approach stems from the fact that existing studies mainly explore indirect relationship between economic activities in distributive trade and economic development, with less focus on the direct impact of distributive trade on economic growth. The paper utilizes information for the period from 2008 to 2015. The research relies on multiple regression model, with the Hausman test its robustness. The results indicate that a hike in turnover per employee in the distributive trade sector by 10 euros per year in one EU member state increases its real economic growth rate by 0.15% in that same year. The significance of the made results is reflected in the fact that the survey takes into account the last economic crisis, and highlights negative effects of final consumption expenditure of general government % GDP on the tangible economic growth rate in EU member states.